THE SECOND WORLD WAR IN AMERICAN LITERATURE - Rayimova Shahina Shermat qizi; Khamitov Eldorbek Erkin O’g’li (TADQIQOTLAR.UZ, 2024)
ABSTRACT. This article provides a brief summary of the information learned about World War II had a profound impact on American literature, shaping the themes, styles, and perspectives of many writers during and after the war.